Modelling marine trophic transfer of radiocarbon (14C) from a nuclear facility. (April 2018) - Tierney, Kieran M.; Heymans, Johanna J.; Muir, Graham K.P.; Cook, Gordon T.; Buszowski, Joe; Steenbeek, Jeroen; Walters, William J.; Christensen, Villy; MacKinnon, Gillian; Howe, John A.; Xu, Sheng
Abstract: Sellafield marine discharges of 14 C are the largest contributor to the global collective dose from the nuclear fuel industry. As such, it is important to understand the fate of these discharges beyond the limitations and scope of empirical analytical investigations for this highly mobile radioactive contaminant. Ecopath with Ecosim (EwE) is widely used to model anthropogenic impacts on ecosystems, such as fishing, although very few EwE studies have modelled the fate of bioavailable contaminants. This work presents, for the first time, a spatial-temporal 14 C model utilising recent developments in EwE software to predict the ecological fate of anthropogenic 14 C in the marine environment. The model predicted observed trends in 14 C activities between different species and through time. It also provided evidence for the integration of Sellafield 14 C in species at higher trophic levels through time. Highlights: Modelling ecosystem uptake of 14C discharges using Ecopath with Ecosim. Spatial-temporal ecosystem model developed with contaminant tracing. Model is capable of reproducing observed trends in 14C activities between species. Model provides evidence for integration of discharged 14C at higher trophic levels. The 14C activity of an organism is dependent on the trophic level it feeds upon.